2017
DOI: 10.1080/00380768.2017.1378569
|View full text |Cite
|
Sign up to set email alerts
|

Forage rice varieties Fukuhibiki and Tachisuzuka emit larger CH4than edible rice Haenuki

Abstract: To determine methane (CH 4) emission differences between edible and forage rice cultivars, we conducted a pot experiment in Yamagata, Japan to grow edible rice Haenuki, and forage rice Fukuhibiki (for feed rice) and Tachisuzuka (for whole-crop silage (WCS) rice) under similar soil and meteorological conditions. The total amounts of N, P, and K fertilizers applied for Fukuhibiki and Tachisuzuka were 1.7, 1.3, and 1.3 times, respectively, higher than those of Haenuki. CH 4 fluxes, and rice plant night respiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…In this same study, the Mn content in the brown rice decreased by 7%, while the polished rice showed a 20.5% decrease in Mn when grown under elevated CO 2 (Ujiie et al, 2019). The vast differences observed in Mn content in different tissues is a significant finding as rice is becoming an important forage crop in some regions of the world (Cheng et al, 2018). While Mn deficiency in forage animals is considered rare, such a significant decrease in micronutrients in the body of the plant suggests that forage animal nutrition will also suffer as a result of rising CO 2 .…”
Section: How Does Elevated Co 2 Affect Micronutrients In C 3 and C 4 mentioning
confidence: 66%
“…In this same study, the Mn content in the brown rice decreased by 7%, while the polished rice showed a 20.5% decrease in Mn when grown under elevated CO 2 (Ujiie et al, 2019). The vast differences observed in Mn content in different tissues is a significant finding as rice is becoming an important forage crop in some regions of the world (Cheng et al, 2018). While Mn deficiency in forage animals is considered rare, such a significant decrease in micronutrients in the body of the plant suggests that forage animal nutrition will also suffer as a result of rising CO 2 .…”
Section: How Does Elevated Co 2 Affect Micronutrients In C 3 and C 4 mentioning
confidence: 66%
“…Livestock production has dominated agricultural land use over the last 50 years, accounting for 65% of the land-use change (Alexander et al 2015). Such change of land use to livestock production (Cheng et al 2018) causes not only increased greenhouse gas emissions (e.g., Gerssen-Gondelach et al 2017;Caro et al 2018), but also local environmental problems, such as eutrophication and water pollution (e.g., Abe et al 2016;Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…High grain yields of protein-rich forage rice have been produced using those novel systems, in which higher yield and rice protein content were achieved using the continuous sub-irrigation system compared with the surface irrigation system 4 . As a result, our cultivation systems are expected to promote the low-cost production of protein-rich forage rice and improve the efficiency of farmland, which inevitably secures domestic livestock production and stops the increase in abandoned farmland that has been observed in Japan since the 1970s 13 .…”
mentioning
confidence: 99%
“…However, forage rice varieties have been recently reported to emit more CH 4 than common staple rice probably owing to the increased biomass production when cultivated under similar growth conditions, which indicates a possible increase in CH 4 emissions from the agricultural sector in Japan owing to the increasing production of forage rice 13 . In addition, an earlier study on wastewater irrigation in rice paddy fields claimed that the increased emissions of CH 4 and N 2 O from wastewater-irrigated fields resulted from the high availability of elements in the wastewater, such as organic C and N 14 .…”
mentioning
confidence: 99%